Does the EFL Textbook for Islamic Senior High School Reflect Islamic Values? A Critical Discourse Analysis - Basya, Dihliza; Afandi, Ahmad Fauzi; Hosim, Mohamad (Universitas PGRI Madiun, 2023)
In Indonesia, the government endorses EFL textbooks for schools, including Islamic Senior High Schools. However, as there is no specific textbook provided that aligns with the religious values needed in these schools, there is potential for a mismatch between the English material taught and the intended educational goals for Islamic Senior High Schools. For this reason, the present critical discourse study aims to investigate the representation of Islamic values in the Indonesian Ministry of Education and Culture-endorsed EFL textbook for Islamic Senior High Schools. The study examines the textbook's content and evaluates the extent to which it reflects Islamic values according to Indonesian cultural and religious norms. Through the analysis by adopting Martin & White’s (2005) language appraisal theory, Kress & Van Leeuwen’s (2020) visual grammar theory, this research seeks to identify any gaps and areas for improvement in the representation of Islamic values in the EFL textbook. This study will contribute to inform the development of EFL textbooks that align with cultural and religious values. Further studies on Islamic values among Indonesian ELT textbooks used in most Islamic schools are deemed necessary to promote more understanding about Islamic principles applied in ELT context.Keywords: Critical Discourse Analysis, EFL Textbook, Islamic Values